Synthesis Algorithm of Proximate Time-Optimal Servo Drive with Constraint of State Coordinates - Derets, Oleksandr; Sadovoi, Oleksandr; Derets, Yevgeniya (2019 IEEE 20th International Conference on Computational Problems of Electrical Engineering (CPEE), 2019)
The N - i switching method made it possible to establish analytical relations between the constraints of the state coordinates of the electric drive and the parameters of sliding mode control systems. This problem is solved for the cases of optimization in time domain and modal control. This paper presents a computational algorithm that implements a parametric synthesis of a control system taking into account changes in the levels of constraints caused by the performance of various shapes transient trajectories.